RTS,S/AS01E immunization increases antibody responses to vaccine-unrelated Plasmodium falciparum antigens associated with protection against clinical malaria in African children: A case-control study - Gyan, B.; Dobaño, C.; Ubillos, I.; Jairoce, C.; Vidal, M.; Jiménez, A.; Santano, R.; Dosoo, D.; Nhabomba, A.J.; Ayestaran, A.; Aguilar, R.; Williams, N.A.; et al. (BMC Medicine, 2019)
Background: Vaccination and naturally acquired immunity against microbial pathogens may have complex interactions that influence disease outcomes. To date, only vaccine-specific immune responses have routinely been investigated in malaria vaccine trials conducted in endemic areas. We hypothesized that RTS,S/A01E immunization affects acquisition of antibodies to Plasmodium falciparum antigens not included in the vaccine and that such responses have an impact on overall malaria protective immunity. Methods: We evaluated IgM and IgG responses to 38 P. falciparum proteins putatively involved in naturally acquired immunity to malaria in 195 young children participating in a case-control study nested within the African phase 3 clinical trial of RTS,S/AS01E (MAL055 NCT00866619) in two sites of different transmission intensity (Kintampo high and Manhiça moderate/low). We measured antibody levels by quantitative suspension array technology and applied regression models, multimarker analysis, and machine learning techniques to analyze factors affecting their levels and correlates of protection. Results: RTS,S/AS01E immunization decreased antibody responses to parasite antigens considered as markers of exposure (MSP142, AMA1) and levels correlated with risk of clinical malaria over 1-year follow-up. In addition, we show for the first time that RTS,S vaccination increased IgG levels to a specific group of pre-erythrocytic and blood-stage antigens (MSP5, MSP1 block 2, RH4.2, EBA140, and SSP2/TRAP) which levels correlated with protection against clinical malaria (odds ratio [95% confidence interval] 0.53 [0.3–0.93], p = 0.03, for MSP1; 0.52 [0.26–0.98], p = 0.05, for SSP2) in multivariable logistic regression analysesConclusions: Increased antibody responses to specific P. falciparum antigens in subjects immunized with this partially efficacious vaccine upon natural infection may contribute to overall protective immunity against malaria. Inclusion of such antigens in multivalent constructs could result in more efficacious second-generation multistage vaccines.
Research Article
Keywords: Malaria; Plasmodium falciparum; Vaccine; RTS,S; Antibody; Pre-erythrocytic antigens; Blood-stage antigens; Naturally acquired immunity; Protection; Maternal antibodies